The Effect of Islamic Social Responsibility Disclosure on Company Performance in Islamic Commercial Bank - Nadia, Nadia; Sahrir, Sahrir; Sari, Nispa (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2026)
This study aims to determine how Islamic Social Responsibility (ISR) affects business operations at Bank Umum Syariah (BUS) in Indonesia. Return on Assets (ROA) is used to measure how much the social responsibility based on Islamic principles contributes to the business's financial performance. This study uses a quantitative approach with an associative design. All BUS listed at Otoritas Jasa Keuangan (OJK) between 2020 and 2024 were included in the study population, and the sample was selected using the purposive sampling technique to increase the availability of lengthy and auditable sustainability and annual reports. Data analysis is carried out using descriptive statistical analysis, classical assumption analysis, linear regression analysis, t, and F. The study's findings indicate that ISR implementation has a positive impact on business operations, although it is not statistically significant, at least not statistically. The study's findings indicate that ISR has a positive impact on business operations, although it is not statistically significant, either in a parallel or parallel manner. This indicates that ISR is unable to provide a significant impact on the profitability of Islamic banks and that other factors, such as operational efficiency and risk financing, have a greater impact on business operations. This study's implications highlight how important it is to improve quality and implement ISR strategies in order to boost stakeholder trust and reputation as well as increase company productivity in the long run.